2012
DOI: 10.1073/pnas.1119719109
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the receptor-binding carboxy-terminal domain of bacteriophage T7 tail fibers

Abstract: The six bacteriophage T7 tail fibers, homo-trimers of gene product 17, are thought to be responsible for the first specific, albeit reversible, attachment to Escherichia coli lipopolysaccharide. The protein trimer forms kinked fibers comprised of an amino-terminal tail-attachment domain, a slender shaft, and a carboxyl-terminal domain composed of several nodules. Previously, we expressed, purified, and crystallized a carboxyl-terminal fragment comprising residues 371-553. Here, we report the structure of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 61 publications
6
93
0
Order By: Relevance
“…Considering that the initial binding of phage to bacteria is mediated by the interaction of its six gp17 tail fibers with bacterial surface receptors, gp17 protein of Yep-phi was expressed and purified as a His 6 fusion (11,34). Consistent with a previous report of T7 (34), we found that the purified recombinant gp17 protein of Yep-phi existed mainly as a multimer in solution. The multimer fraction was SDS resistant unless previously boiled (Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Considering that the initial binding of phage to bacteria is mediated by the interaction of its six gp17 tail fibers with bacterial surface receptors, gp17 protein of Yep-phi was expressed and purified as a His 6 fusion (11,34). Consistent with a previous report of T7 (34), we found that the purified recombinant gp17 protein of Yep-phi existed mainly as a multimer in solution. The multimer fraction was SDS resistant unless previously boiled (Fig.…”
Section: Resultssupporting
confidence: 63%
“…2A). The alignment shows a highly conserved N-terminal moiety (amino acids 1 to 149), which belongs to domain family PHA00430 (34), indicating that they have the same mechanism of attaching the fiber to the phage as numerous T7-related phages. Aside from this region, the other sequence of the Yep-phi subgroup diversified from that of the other three (T7, T3, and PhiA1122).…”
Section: Resultsmentioning
confidence: 99%
“…For example, phage T7 has 6 tail fibers, 109,162,165 which interact with the 6-fold-symmetric and 12-fold symmetric tube proteins (Fig. 17B), whereas phage φ29 has 12 spindle-shaped tail spikes attached via the 12-foldsymmetric tube protein (Fig.…”
Section: Organization Of the Shortmentioning
confidence: 99%
“…The C-terminal portion of the fiber protein (gp17) is considered essential for virus-receptor interaction (12). To determine the structural component that interacts with rough LPS, we incubated rough LPS with recombinant fiber-less tail complexes and with fiber-containing tail complexes (13).…”
Section: T7 Ejects Its Dna Genome In Vitro In the Presence Of Roughmentioning
confidence: 99%
“…At least four proteins (gp8, gp11, gp12, and gp17) make up the T7 tail, which forms a central tubular structure with a closed, twisted nozzle at the bottom formed by a gp12 hexamer. This tubular assembly is surrounded by six protruding fibers specializing in receptor recognition, each of which is a gp17 trimer (12,13). Both proteins are docked to the connector (gp8) by a dodecameric ring termed adaptor or gatekeeper (gp11).…”
mentioning
confidence: 99%